Study about Mid-Evaluation of the Watershed Programme (IWDP- III) in Salem District, India - Sasikala, R.; Premavathi, R. (Research Advances and Challenges in Agricultural Sciences Vol. 8, 2024)
The present study aims to ensure the availability of drinking water, fuel wood and fodder and raise income and employment for farmers and landless labourers through improvement in agricultural production and productivity. Indian agriculture is predominantly rainfed agriculture out of 143 million hectares of total cultivated area in the country, 101 million ha (i.e. nearly 70 per cent) area are rainfed and about 42% of dry land areas contribute for total food grain production. Rainfall distribution and amount variations affect farmers' socioeconomic circumstances and crop productivity. The Watershed Management Program has given emphasis to the conservation of natural resources in order to counteract unfavourable conditions and support farmers. Mid-term evaluation of IWDP- III batch watersheds was conducted in all the ten watershed villages spread over in Valapady block of Salem district in two phases; (i) Information was gathered from the Project Implementing Agency (PIA) and discussion was made with members of the Watershed Committee and Watershed Development Team (WDT) (ii) Field study was done and interaction was made with the beneficiaries of the area where IWDP- III watershed programme was implemented. And also using a simple random sampling technique, 100 beneficiaries were selected to study the community participation in implementing the watershed activities. The data were collected with a well-structured interview schedule. Percentage analysis was used for data analysis. On the whole, it was observed that 85% of the community participation was at full level in planning the work. The majority (82.4%) of the village community showed their full participation in decision making activities. Eighty per cent of the village community showed full participation in the site selection process and regarding the execution of work, 76.4% of the community showed full participation. It shows that the community people were well aware of the importance of the watershed programme and they were involved in the implementation of the programme at all stages of the programme. In general, it was observed that in the area where watershed structures are undertaken, there was a reduction in soil erosion. Under afforestation and pasture development agro forestry plantation, jatropa plantation and fodder crop demonstration were also done to increase the income of the village community. They were also aware that if the watershed programme is implemented in their village it would recharge the groundwater level which in turn would improve their livelihood so the majority of the community people participated in implementing the watershed activities.